Long-term progression and risk factors of fundus tessellation in the Beijing Eye Study - Yan, Yan Ni; Jonas, Jost B. (Scientific reports, 2018)
To assess the progression of fundus tessellation, color fundus photographs of the participants of the longitudinal population-based Beijing Eye Study were examined. The study included 4439 subjects in 2001 and 2695 (66.4% of the surviving) individuals in 2011. Larger progression in macular fundus tessellation (mean: 0.24 ± 0.48 grades) was associated (multivariate analysis; correlation coefficient r: 0.53) with thinner subfoveal choroidal thickness in 2011 (P < 0.001; standardized regression coefficient beta: −0.37), older age (P < 0.001; beta: 0.22), higher level of education (P < 0.001; beta: 0.09), more myopic change in refractive error (P < 0.001; beta: −0.09) and lower cognitive function score (P = 0.02; beta: −0.05). Larger increase in peripapillary fundus tessellation (mean: 0.19 ± 0.26 grades) correlated with thinner peripapillary choroidal thickness in 2011 (P < 0.001; beta: −0.35), older age (P < 0.001; beta: 0.20), worse best corrected visual acuity (P = 0.001; beta: 0.07), more myopic change in refractive error (P < 0.001; beta: −0.07) and higher prevalence of ever smoking (P = 0.004; beta: 0.05). The increase in macular fundus tessellation, as a surrogate for thinning of the posterior choroid, was associated with lower cognitive function, after adjusting for choroidal thickness, age, educational level and change in refractive error. The findings point to the clinical value of the assessment of fundus tessellation and suggest potential associations between cognitive function and fundus tessellation/choroidal thickness.
Gesehen am 09.12.2020